Analisis Potensi Dan Pengembangan Objek Wisata Di Kabupaten Grobogan - Prawita Sari, Menuk, Dr. Kuswaji Dwi Priyono,M. Si (2017)
Grobogan has a number of potential tourist sites. There are several objects that have been maintained and has not been maintained, so necessary to the penialian potential. The purpose of this study was (1) to analyze the potential of tourism in Grobogan, (2) identify the dominant factors that influence the potential tourist sites in Grobogan, and (3) create a tourism development strategy in Grobogan. The method used in this study is a survey method. Data analysis techniques using qualitative descriptive. The results of this study are (1) most of the tourist sites in Grobogan has high combined potential, such as: tourist site of Api Abadi Mrapen, Bledug Kuwu, Kedung Ombo, Goa Lawa or Goa Macan, Sendang Coyo, and Sendang Keongan, Meanwhile it is a tourist sites with a combined potential level of being is a tourist sites Air Terjun and tourism sites with a low combined potential contained in Goa Urang. Nevertheless, according to the potential of internal, external, and potential supporters of attraction level potential is still varied ranging from low to high, (2) the dominant factors that cause the level of high potential in Grobogan is a condition factors attractions, and the availability of complementary facilities attractions and (3) strategy of tourism development in Grobogan directed as follows: (a) improve the quality of the object, by utilizing the natural resources that exist with regard to aspects of environmental sustainability, (b) increase efforts to promote travel (c) increase the intensity attractive tourist event, and (d) the establishment of zoning Key words: tourist potential, development strategy, SWOT, Grobogan